Women in Brazilian neurosurgery - Ivamoto, Henrique S. (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2010)
Medicine remained as a male profession during many centuries, but the proportion of women rose steadily during the second part of the 20th century in the world and in Brazil. In 2006 they became the majority (51.75%) of the new physicians licensed by the Regional Council of Medicine of the State of São Paulo. Nevertheless, the proportion of women in Neurosurgery and in directive posts in entities of the specialty in Brazil continue very low or absent. Data obtained from the Brazilian Society of Neurosurgery and the Brazilian Academy of Neurosurgery are very similar to those of the American counterparts, like the proportion of women among the associates, around 5%, and one single female chief of a service certified for training in each country. Authors from WINS, an American entity, reported several problems suffered by female neurosurgeons, including gender discrimination. Such occurrences, as reported in online news, should alert against discriminatory attitudes.
Keywords: Women physicians; Neurosurgery; Statistics